Diaphragm and secondary battery

By intermittently coating the polymer layer intermittently in the corner area of ​​the lithium -ion battery, and the groove is set to solve the problem of being suffered from large tension and squeezing pressure in the cycling of the battery in the cycle, the stability and stability of the diaphragm and the stability and the diaphragm Improvement of battery cycle performance.

CN119381700AActive Publication Date: 2025-01-28ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411552663.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-28
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

During the recycling process of existing lithium-ion batteries, the chain reaction caused by the expansion of the anode inside the battery cell causes the diaphragm to bear excessive tension and squeeze pressure in the corner area, which may cause diaphragm to rupture and ion transmission path to break, forming black The lithium splatinization phenomenon damages the circulating performance of the battery.

Method used

Design a diaphragm, only coating the polymer layer intermittently in the corner area of ​​the rim electrode component, and set multiple grooves in the polymer layer to ensure that the polymer layer will not be excessively squeezed or pulled during the scrolling process. Extending to reduce damage to the diaphragm.

Benefits of technology

Effectively alleviate the risk of damaging the diaphragm during the electrode component wound, ensure the stability of the partials, avoid the occurrence of the "dark spots lithium" phenomenon, and improve the cycle stability and service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381700A_ABST
    Figure CN119381700A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of secondary batteries, and mainly relates to a diaphragm which is suitable for a winding type electrode assembly, the electrode assembly is provided with a corner area in a bent state, the diaphragm comprises a base film, the base film in a flattened state comprises straight sections and sections to be bent, the straight sections and the sections to be bent are sequentially and alternately connected in the length direction of the base film, and the sections to be bent correspond to the corner area; the first coatings are arranged on the two surfaces of the base film in the thickness direction of the base film respectively; the second coating is arranged on at least one surface of the base film in the thickness direction of the base film, and the second coating is arranged between the base film and the first coating; the second coating comprises a plurality of polymer layers which are arranged at intervals in the length direction of the base film; the polymer layer corresponds to the to-be-bent section; wherein at least one polymer layer is provided with at least two grooves; according to the preparation method, the polymer layer is intermittently coated, so that the extrusion force on the diaphragm is relieved; in addition, the invention designs the secondary battery comprising the diaphragm, and the stability of the secondary battery is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of secondary batteries, and mainly relates to a diaphragm and a secondary battery. Background Art

[0002] Lithium-ion batteries have been widely used in many fields such as consumer electronics, energy storage systems and new energy vehicles due to their excellent energy density, long and stable cycle life and environmental protection characteristics. At present, most lithium-ion battery cells adopt a winding structure, and many improvements have been made to the battery poles and diaphragms to solve the problem of lithium deposition at the corners during the winding process of the poles.

[0003] Under the current technical background, in response to the technical problem of "lithium deposition at corners", industry experts generally tend to coat the surface of the battery cell diaphragm with a material with a specific compression ratio to reduce the pressure on the pole piece during the winding process. However, it is worth noting that the above solution does not fully consider the chain reaction caused by the expansion of the anode and cathode inside the battery cell during the cycle of the battery. Specifically, the expansion will increase the tension and extrusion force of the coating layer on the diaphragm in the corner area. At this time, the coating design originally intended to relieve pressure may be counterproductive and have an adverse effect on the diaphragm, which may lead to serious consequences such as diaphragm rupture and ion transmission path breakage, forming the "black spot lithium deposition" phenomenon, and ultimately damaging the battery's cycle performance.

[0004] Based on this, it is urgent to improve the existing diaphragms and secondary batteries to solve the defects of the aforementioned technologies. Summary of the invention

[0005] One of the purposes of the present invention is to improve the coating structure of the battery diaphragm in order to overcome the technical problem that the prior art adopts coating of a polymer layer and a first coating on both sides of the diaphragm, while ignoring that the polymer layer and the first coating will also cause a certain degree of extrusion in the corner area during the battery cycle.

[0006] In order to achieve the above technical objectives, this application adopts the following technical solutions:

[0007] A diaphragm is applicable to a wound electrode assembly, wherein the electrode assembly has a corner region in a curved state, and the diaphragm comprises:

[0008] The base film, in a flattened state, comprises straight sections and sections to be bent that are alternately connected in sequence along the length direction of the base film, and the sections to be bent correspond to the corner areas;

[0009] The first coating layer is respectively arranged on two surfaces of the base film along the thickness direction thereof;

[0010] A second coating layer is disposed on at least one side of the base film along the thickness direction thereof, and the second coating layer 4 is disposed between the base film and the first coating layer;

[0011] The second coating layer includes a plurality of polymer layers, and the plurality of polymer layers are arranged at intervals along the length direction of the base film; the polymer layers are arranged corresponding to the sections to be bent;

[0012] Wherein, at least one polymer layer is provided with at least two grooves.

[0013] Through the above technical solution, the following technical effects are produced:

[0014] First of all, the present application only coats the polymer layer on the base film in the corner area of ​​the wound electrode assembly, and each polymer layer in the corner area is intermittently coated with many grooves. This design not only effectively reduces the loss of the polymer layer coated in the non-corner area of ​​the wound electrode, but also avoids the polymer layer from being compressed or stretched during the winding process of the wound battery cell electrode sheet, causing the polymer layer to exert other forces on the diaphragm and the battery cell in the corner area, further effectively alleviating the risk of the diaphragm being damaged due to extrusion during the winding process of the electrode assembly, thereby ensuring the working stability of the diaphragm.

[0015] As a further improvement to the diaphragm of the present invention, the electrode assembly includes a pole piece in a wound structure, which is in contact with the diaphragm; the length of the polymer layer corresponding to the section to be bent is L1, and the diaphragm has a recessed area and a raised area in the section to be bent, and the arc length of the raised area is L2, wherein L1 and L2 satisfy: L2≥L1≥0.8L2.

[0016] As a further improvement to the diaphragm of the present invention, the arc diameter of the raised area of ​​the innermost layer of the diaphragm to be bent is Ds0, and the arc length L corresponding to the raised area of ​​the innermost layer of the diaphragm to be bent is 21 Meet L 21 =π(Ds0) / 2.

[0017] As a further improvement of the diaphragm of the present invention, the number of winding layers of the diaphragm is n, and the arc length L of the convex area corresponding to the winding Nth layer of the diaphragm in the bending section is 2n Meet L 2n =π(Ds0+(N-1)△t) / 2;

[0018] Among them, for each additional layer of the diaphragm wound on the basis of the innermost layer, the increase in the arc diameter corresponding to the convex area of ​​the diaphragm in the to-be-bent section relative to the arc diameter corresponding to the convex area of ​​the adjacent inner diaphragm in the to-be-bent section is △t.

[0019] As a further improvement to the diaphragm of the present invention, along the length direction of the polymer layer, the width of the groove increases first and then decreases, and the width of the groove corresponding to the length center of the section to be bent is the largest.

[0020] As a further improvement to the diaphragm of the present invention, the width of the groove is D1, and D1 satisfies: 0.9 mm-1.1 mm.

[0021] As a further improvement to the diaphragm of the present invention, along the length direction of the polymer layer, the depth of the groove increases first and then decreases, and the depth of the groove corresponding to the length center of the section to be bent is the largest.

[0022] As a further improvement to the diaphragm of the present invention, the depth of the groove is D2, and D2 satisfies: 0.5 micrometers-10 micrometers.

[0023] As a further improvement to the separator of the present invention, the polymer layer includes an emulsion of polymer particles, a dispersion aid, and an adhesive;

[0024] The emulsion of polymer particles is one or more of polyethylene emulsion, polyethylene microwax emulsion, polyvinylidene fluoride emulsion, polytetrafluoroethylene emulsion, polymethyl methacrylate emulsion, polyimide emulsion, polystyrene emulsion and polyacrylamide emulsion;

[0025] The dispersing auxiliary agent is one or more of polyacrylic acid and its sodium salt, polyacrylamide, polyvinyl alcohol, sodium citrate, sodium ethylenediaminetetraacetate, sodium diacetate, sodium hexametaphosphate, sodium silicate, and carboxymethyl cellulose;

[0026] The adhesive is a polypropylene adhesive.

[0027] As a second technical purpose of the present invention, in order to overcome the defects of the prior art, a secondary battery with higher working stability is provided.

[0028] In order to achieve the above technical objectives, this application adopts the following technical solutions:

[0029] A secondary battery comprises any of the above-mentioned separators.

[0030] Through the above technical solution, the following technical effects are produced:

[0031] Thanks to the diaphragm provided by the present invention, by intermittently coating a polymer layer on each corner area of ​​the electrode assembly, during the winding process of the wound battery cell or when the battery is subjected to external force, the diaphragm and the electrode piece in the corner area will not be affected by the force of the polymer layer due to compression or stretching of the polymer layer. At the same time, the external force on the diaphragm and the electrode piece is also effectively alleviated, and the occurrence of the "black spot lithium precipitation" phenomenon is effectively avoided, thereby improving the cycle stability of the battery and extending its service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0033] Figure 1It is a schematic diagram of the diaphragm structure in the present invention;

[0034] Figure 2 It is a schematic diagram of the structure of the electrode assembly in the present invention;

[0035] Figure 3 for Figure 2 A magnified view of middle;

[0036] Figure 4 It is a schematic diagram of the structure of the pole piece and the diaphragm in the present invention;

[0037] Figure 5 It is a curve diagram of the normal temperature cycle capacity retention rate of the battery in Example 1 of the present invention and Comparative Example 1;

[0038] Figure 6 It is a curve diagram of the thickness expansion rate of the battery in Example 1 of the present invention and Comparative Example 1 during normal temperature cycling.

[0039] in:

[0040] 1-basement membrane;

[0041] 11-straight section;

[0042] 12-segment to be bent;

[0043] 2- wound electrode assembly;

[0044] 21- Corner area;

[0045] 22-pole piece;

[0046] 3- first coating;

[0047] 4- Second coating;

[0048] 41- polymer layer;

[0049] 411-Groove. DETAILED DESCRIPTION

[0050] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by technicians in the technical field of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application.

[0051] In the description of the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected" and "fixed" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0052] Although the present application is disclosed as above in the form of a preferred embodiment, it is not intended to limit the claims. Any person skilled in the art may make several possible changes and modifications without departing from the concept of the present application. Therefore, the scope of protection of the present application shall be based on the scope defined by the claims of the present application.

[0053] It is known that the winding methods of the existing wound electrode assembly 2 are Z-winding and J-winding. Regardless of the winding method, the essence of the winding is to wind the pole piece 22 and the diaphragm in the wound electrode assembly 2 layer by layer from the winding center to the outside. In the winding process, bending areas are formed on both sides of the wound battery cell, and the diaphragm and the pole piece 22 in this area show a specific curvature bending state. In the process of forming this bending state, the corner area 21 of the wound electrode assembly 2 becomes the focus of the main concentration of bending force, among which the pole piece 22 and the diaphragm are particularly significant. However, since the non-corner area 21 of the wound electrode assembly 2 has a small bending amplitude (in this application, the non-corner area 21 is approximately set as a straight area), the effect of its bending curvature on the battery cell can be ignored. Furthermore, during the battery charge and discharge cycle, the pole piece 22 and the diaphragm in the corner area 21 will experience expansion and contraction, further aggravating the accumulation of stress, thereby increasing the stress load at the corner. In particular, the negative electrode of the battery will expand in volume due to the insertion and extraction of lithium ions during the cycle, which makes the diaphragm more susceptible to breakage and deformation, and may even lead to lithium precipitation (i.e., lithium metal is deposited at the corners, affecting battery performance and safety).

[0054] Based on this, the technicians in this field proposed to coat the polymer layer 3 and the first coating 3 on both sides of the base film 1, respectively, so as to alleviate the force on the diaphragm and the pole piece 22 during the bending process of the wound battery cell. However, the technicians in this field did not take into account that even if the polymer material with a compression ratio of 80% exists in the bending process, the polymer layer 3 located in the concave area of ​​the diaphragm to be bent section 12 will produce an outward thrust due to excessive extrusion, and this thrust will directly act on the diaphragm to affect the performance of the diaphragm or even damage the diaphragm; and the polymer layer 3 coated on the convex area of ​​the diaphragm to be bent section 12 will produce a retraction force due to excessive stretching (due to the nature of the polymer layer 3 itself), which will further act on the outside of the diaphragm to affect the performance of the diaphragm. In addition, because the inner concave area and the convex area of ​​the diaphragm generate forces in different directions or the same direction, and these two forces can act on both sides of the diaphragm, the diaphragm is subjected to uneven forces inside and outside, thereby further increasing the risk of the diaphragm being damaged.

[0055] The inventors of the present application observed the above technical problems in experiments, and thus came up with an idea for solving the above technical problems, namely, each polymer layer 3 coated in the diaphragm in the bending area of ​​the wound battery cell is intermittently treated, and a certain position is reserved so that the polymer layer 3 of the wound battery cell will not be over-extended or over-stretched during the winding process, thereby causing damage to the diaphragm and the electrode 22.

[0056] like Figure 1-4 As shown, in order to alleviate the force that occurs between the diaphragm and the pole piece 22 in the prior art during the bending process, and at the same time, the coating that alleviates the force will further produce other negative effects on the diaphragm and the pole piece 22, the present application makes improvements to the diaphragm,

[0057] Specifically, the diaphragm of the present application is suitable for a wound electrode assembly 2, the wound electrode assembly 2 has a corner area 21 in a curved state, and the diaphragm includes:

[0058] The invention is suitable for a wound electrode assembly, wherein the electrode assembly has a corner area 21 in a bent state, and the diaphragm comprises: a base film 1, in a flattened state, along the length direction of the base film 1, the base film 1 comprises a straight section 11 and a section to be bent 12 which are alternately connected in sequence, and the section to be bent 12 corresponds to the corner area 21; a first coating 3, respectively arranged on two surfaces of the base film 1 along its thickness direction; a second coating 4, arranged on at least one side of the base film 1 along its thickness direction, and the second coating 4 is arranged between the base film and the first coating 3; the second coating 4 comprises a plurality of polymer layers 41, and the plurality of polymer layers 41 are arranged at intervals along the length direction of the base film 1; the polymer layer 41 is arranged corresponding to the section to be bent 12; by coating the polymer layer 3 only between the base film corresponding to the corner area 21 and the first coating 3, consumables of coating material are saved, and at the same time, the increase in thickness of the wound battery cell caused by coating an excessive amount of polymer layer 3 on the straight section 11 of the base film 1 is avoided. (If the thickness increases, it will further affect the force and bending radius of the corner area 21 during the winding process of the wound battery cell, thereby causing irreversible effects on the diaphragm and pole piece 22 in the corner area 21).

[0059] Furthermore, in the polymer layer 3 coated with the diaphragm of the present application, at least one polymer layer 3 is provided with at least two grooves 411. The grooves 411 are generated in the form of intermittent coating during the coating process of the polymer layer 3. The depth of the groove 411 may be the same as the depth of the polymer layer 3 or may be slightly less than the thickness of the polymer layer 3. That is, the intermittent coating of the polymer layer 3 may choose not to directly coat the polymer layer 3 in the groove 411 area, or may intermittently coat a small amount of coating in the groove 411 area to produce a groove 411 with a depth less than the thickness of the polymer layer 3. Through the above design, the diaphragm prepared in the present application participates in the winding process of the wound battery cell, so that the polymer layer 3 is more reasonably distributed and stress relieved in the concave area and the convex area of ​​the bending section due to the presence of the groove 411. In the depressed area, the design of the groove 411 makes it difficult for the polymer layer 3 in this area to generate an outward thrust due to excessive extrusion, thereby reducing the negative impact on the performance of the diaphragm. In the raised area, although the polymer layer 3 will be deformed due to stretching, the presence of the groove 411 helps to disperse the stretching force and prevent the stretching force generated by excessive stretching from directly affecting the outer side of the diaphragm. At the same time, the provision of the groove 411 makes the force on the inner and outer sides of the diaphragm more uniform during the bending process, reducing the risk of damage caused by uneven force.

[0060] Furthermore, by providing the groove 411 in the polymer layer 3, not only the stress between the separator and the pole piece 22 during the bending process is effectively relieved, but also the increase in the thickness of the battery cell caused by excessive coating of the polymer layer 3 in unnecessary areas is avoided. This design not only ensures the safety of the battery, but also optimizes the thickness of the wound battery separator, thereby further alleviating the bending force in the bending area.

[0061] Furthermore, the pole assembly includes a pole piece in a winding structure, and the pole piece is in contact with the diaphragm; the length of the polymer layer corresponding to the section to be bent is L1, and the diaphragm has a concave area and a convex area in the section to be bent, and the arc length of the convex area is L2, where L1 and L2 satisfy: L2≥L1≥0.8L2. By controlling the arc length of the convex area corresponding to the section to be bent 12 and the length of the corresponding polymer layer 3, the polymer layer 3 can be entirely coated only on the corner area 21, so that this setting not only ensures that the polymer layer 3 can fully cover and protect the corner area 21 of the pole piece 22 that is most vulnerable to damage during the winding process, but also avoids unnecessary over-coating. Specifically, under this proportional control, the polymer layer 3 is limited to the key position that needs to be enhanced, that is, the part with a longer arc length corresponding to the convex area. This targeted coating method not only effectively improves the durability of the diaphragm in a complex bending environment, but also significantly reduces the overall weight and material cost of the battery cell. Because the amount of polymer used in non-critical areas is reduced, the battery cell can be more compact and the energy density is correspondingly improved.

[0062] like Figure 1-4 As shown, in order to further improve the utilization rate of the polymer layer of the present application, specifically, the arc diameter of the raised area of ​​the innermost layer of the diaphragm to be bent is Ds0, and the arc length L corresponding to the raised area of ​​the innermost layer of the diaphragm to be bent is 21 Meet L 21 =π(Ds0) / 2. Assuming Ds0 is 10 mm, then L 11 About 15.7 mm. As the winding process progresses, the diameter of the arc formed by the diaphragm in the subsequent winding will gradually increase, but the corresponding arc length L1 must still meet the condition of L2≥L1≥0.8L2 to ensure effective coverage of the polymer layer 3 and avoid excess. This design detail ensures that the polymer layer 3 can provide just the right amount of protection at different winding stages, neither excessive nor insufficient.

[0063] Specifically, when the number of winding layers of the diaphragm is set to N, the arc length L of the convex area corresponding to the winding Nth layer of the diaphragm in the bending section is 2n Meet L 2n=π(Ds0+(N-1)△t) / 2; wherein, for each additional layer of the diaphragm wound on the basis of the innermost layer, the increase in the diameter of the arc corresponding to the raised area of ​​the diaphragm in the section to be bent relative to the diameter of the arc corresponding to the raised area of ​​the adjacent inner diaphragm in the section to be bent is △t. Taking a battery with 18 core layers as an example for calculation, the thickness of the positive electrode sheet 22 is 0.088 mm, the thickness of the negative electrode sheet 22 is 0.105 mm, the thickness of the base film 1 is 0.004 mm, the thickness of the oily coating layer (the first coating 3 in this application) coated on one side is 0.0015 mm (double-sided), the thickness of the intermittently coated polymer layer 3 is 0.001 mm, and the total thickness of the diaphragm is 0.009 mm. The arc diameter of the diaphragm at the corner of the first layer of this model is Ds0=1.2561 mm, and the increase amplitude of the arc diameter of the diaphragm at the corner is △t=0.211 mm. The design parameters of the polymer layer 3 coated at the corner of the diaphragm are shown in Table 1:

[0064]

[0065]

[0066] Table 1

[0067] Further, the width of the groove 411 of the polymer layer 3 in the present application shows a trend of first increasing and then decreasing along the length direction of the polymer layer 3 (ie, the X direction). Specifically, the width of the groove 411 corresponding to the center of the length (ie, the X direction) of the section to be bent 12 in the polymer layer 3 reaches the maximum value. It should be clearly pointed out that if the groove 411 is not directly set at the center of the length of the section 12 to be bent, that is, with the center of the length of the section as the axis, the width of the groove 411 closest and symmetrical on both sides will be regarded as the maximum. Furthermore, if there is neither a directly corresponding groove 411 at the center of the length of the section 12 to be bent, nor a groove 411 designed symmetrically on both sides of the central axis, the groove 411 closest to the center axis of the length of the section 12 to be bent is selected, and its width will be regarded as the maximum value in the area. Through this design, the polymer layer 3 located in the recessed area of ​​the diaphragm to be bent 12 of the present application will generate an outward thrust due to excessive extrusion, and the polymer layer 3 coated on the convex area of ​​the diaphragm to be bent 12 will generate a retraction force due to excessive stretching.

[0068] Specifically, the width of the groove 411 is D1, and D1 satisfies: 0.9 mm-1.1 mm. In a specific implementation process, the width of the groove 411 can be: 0.9 mm, 0.91 mm, 0.92 mm, 0.93 mm, 0.94 mm, 0.95 mm, 0.96 mm, 0.97 mm, 0.98 mm, 0.99 mm, 1.00 mm, 1.01 mm, 1.02 mm, 1.03 mm, 1.04 mm, 1.05 mm, 1.06 mm, 1.07 mm, 1.08 mm, 1.09 mm, 1.10 mm.

[0069] Furthermore, the depth of the groove 411 of the polymer layer 3 in the present application shows a trend of first increasing and then decreasing along the length direction of the polymer layer 3 (i.e., the X direction). Specifically, the depth of the groove 411 corresponding to the length direction center of the section 12 to be bent in the polymer layer 3 reaches a maximum value. It should be clearly pointed out that if the groove 411 is not directly set at the length direction center of the section 12 to be bent, that is, with the center of the length center of the section as the axis, the depth of the groove 411 closest and symmetrical on both sides will be regarded as the maximum. Furthermore, if there is neither a directly corresponding groove 411 at the length direction center of the section 12 to be bent, nor a groove 411 designed symmetrically on both sides along the length direction center axis, the groove 411 closest to the length direction center axis of the section 12 to be bent is selected, and its depth will be regarded as the maximum value in the area.

[0070] Through this design, the thickness of the polymer layer 3 located in the concave area or the convex area of ​​the diaphragm to be bent section 12 of the present application can be reduced. Since the present application has found through experiments that when the thickness of the polymer layer 3 corresponding to the groove 411 is relatively small, not only the protection of the diaphragm by the polymer layer 3 is ensured, but also because the polymer protrusion here is relatively thin, therefore, in the present application, when the diaphragm and the pole piece 22 are bent during the winding process, the polymer layer 3 at the groove 411 corresponding to the concave area will not generate a significant extrusion force, thereby avoiding a large outward thrust caused by excessive extrusion of the polymer layer 3.

[0071] At the same time, when the depth of the groove 411 corresponding to the concave area is the largest, its surface area is also increased accordingly, which is sufficient to disperse the outward thrust generated, thereby reducing the possible damage to the diaphragm. In the present application, when the diaphragm and the pole piece 22 are bent during the winding process, the polymer layer 3 at the groove 411 corresponding to the convex area will not generate a significant stretching force. At the same time, when the depth of the groove 411 corresponding to the convex area is the largest, the thickness of the polymer layer 3 corresponding to the groove 411 also decreases, and then the tensile force generated is also reduced. Furthermore, when the thickness of the polymer layer 3 located in the concave area or the convex area of ​​the diaphragm to be bent section 12 is thin, it can also effectively reduce the internal stress generated by the battery during the charging and discharging process, thereby improving the cycle life and safety of the battery.

[0072] Specifically, the depth of the groove 411 is D2, and the depth of the groove 411 is D2, and D2 satisfies: 0.5 micron-10 micron. In the specific implementation process, the depth of the groove 411 can be: 0.5 micron, 0.6 micron, 0.7 micron, 0.8 micron, 0.9 micron, 1.0 micron, 1.1 micron, 1.2 micron, 1.3 micron, 1.4 micron, 1.5 micron, 1.6 micron, 1.7 micron, 1.8 micron, 1.9 micron, 2.0 micron, 2.1 micron, 2.2 micron, 2.3 micron, 2.4 micron, 2.5 micron, 2.6 micron m, 2.7 microns, 2.8 microns, 2.9 microns, 3.0 microns, 3.1 microns, 3.2 microns, 3.3 microns, 3.4 microns, 3.5 microns, 3.6 microns, 3.7 microns, 3.8 microns, 3.9 microns, 4.0 microns, 4.1 microns, 4.2 microns, 4.3 microns, 4.4 microns, 4.5 microns, 4.6 microns, 4.7 microns, 4.8 microns, 4.9 microns, 5.0 microns, 5.1 Micron, 5.2 micron, 5.3 micron, 5.4 micron, 5.5 micron, 5.6 micron, 5.7 micron, 5.8 micron, 5.9 micron, 6.0 micron, 6.1 micron, 6.2 micron, 6.3 micron, 6.4 micron, 6.5 micron, 6.6 micron, 6.7 micron, 6.8 micron, 6.9 micron, 7.0 micron, 7.1 micron, 7.2 micron, 7.3 micron, 7.4 micron, 7.5 micron, 7. 6 microns, 7.7 microns, 7.8 microns, 7.9 microns, 8.0 microns, 8.1 microns, 8.2 microns, 8.3 microns, 8.4 microns, 8.5 microns, 8.6 microns, 8.7 microns, 8.8 microns, 8.9 microns, 9.0 microns, 9.1 microns, 9.2 microns, 9.3 microns, 9.4 microns, 9.5 microns, 9.6 microns, 9.7 microns, 9.8 microns, 9.9 microns, 10.0 microns. Through this design of controlling the width and depth of the groove 411, the adaptability and stability of the polymer layer 3 in the bending area of ​​the diaphragm can be ensured, thereby improving the performance and safety of the battery as a whole. However, it should be noted that the depth of the groove 411 of the present application will not be greater than the thickness of the polymer layer 3, which is determined by the fact that the groove 411 is essentially a product of the principle of controlling the thickness of the local polymer layer 3.

[0073] Furthermore, the first coating 3 in the present application is an oily coating layer, including PVDF and ceramic materials, PVDF is polyvinylidene fluoride. Specifically, considering the thickness requirements of the wound electrode assembly 2, the present application only applies the first coating 3 on one side of the thickness direction of the base film 1 to achieve the bonding between the diaphragm and the pole piece 22, while reducing the impact on the battery thickness, and further helps to maintain the stability of the wound electrode assembly 2 during the battery charging and discharging process. Among them, the number of the first coating 3 is less than or equal to the number of straight sections 11 of the base film 11. When the number is equal, each straight section 11 is coated with the first coating 3 to ensure good bonding between the pole piece 22 and the diaphragm, while not significantly increasing the total thickness of the battery. In the specific implementation process, the diaphragm of the present application can be used in conjunction with various types of positive and negative electrode materials, such as lithium cobalt oxide (Li CoO2), lithium nickel cobalt manganese oxide (NCM), lithium iron phosphorus (LFP), etc. Specifically, by optimizing the coating distribution of the diaphragm, the present application not only improves the cycle stability of the wound electrode assembly 2 , but also can adapt to the winding forms of different wound electrode assemblies 2 .

[0074] Furthermore, the polymer layer 3 in this application refers to a coating including an emulsion of polymer particles, a dispersion aid and an adhesive. In the specific implementation process, the polymer layer includes an emulsion of polymer particles, a dispersion aid and an adhesive; the emulsion of polymer particles is one or more of polyethylene emulsion, polyethylene microwax emulsion, polyvinylidene fluoride emulsion, polytetrafluoroethylene emulsion, polymethyl methacrylate emulsion, polyimide emulsion, polystyrene emulsion, and polyacrylamide emulsion; the dispersion aid is one or more of polyacrylic acid and its sodium salt, polyacrylamide, polyvinyl alcohol, sodium citrate, sodium ethylenediaminetetraacetate, sodium diacetate, sodium hexametaphosphate, sodium silicate, and carboxymethyl cellulose; the adhesive is a polypropylene adhesive. The above-mentioned materials have a certain compressibility, and the material compression ratio is 20% to 90%.

[0075] In order to further reflect the improvement of the diaphragm structure by the above-mentioned technical scheme in the present application, the diaphragm material shown in Examples 1-5 and the diaphragm material shown in Comparative Examples 1-3 are designed by controlling variables. Bare cells are obtained by winding the diaphragm materials of Examples 1-5 and Comparative Examples 1-2 with the positive and negative electrode sheets 22 after film preparation, and the wound bare cells are packaged, baked, injected, formed, sealed, and divided to obtain finished cells. By testing the capacity retention rate and thickness expansion rate of the cells prepared in Examples 1-5 and Comparative Examples 1-2, respectively, the performance difference between the cells prepared by the diaphragm of the present application and the cells prepared by the existing diaphragms can be more clearly understood.

[0076] Example 1

[0077] Taking the battery cell with N=18 layers as an example, the thickness of the positive electrode sheet 22 is 0.088 mm, the thickness of the negative electrode sheet 22 is 0.105 mm, the thickness of the base film 1 is 0.004 mm, the double-sided coating thickness of the first coating 3 (oily coating layer) is 0.0015 mm, the double-sided coating thickness of the polymer layer 3 is 0.001 mm, the coating method of the polymer layer 41 is intermittent coating, the maximum width of the groove 411 in the intermittent coating is 0.9 mm, the maximum depth of the groove 411 in the intermittent coating is 0.0008 mm, the total thickness of the diaphragm is 0.009 mm, the arc diameter of the diaphragm at the corner of the first layer of this model is Ds0=1.2561 mm, and the increase in the arc diameter of the diaphragm at the corner is △

[0078] t = 0.211 mm.

[0079] Example 2

[0080] Different from Example 1, the coating thickness of the polymer layer 3 on both sides of the battery separator in this embodiment is 0.0001 mm, wherein the coating method of the polymer layer 41 is intermittent coating, and the maximum depth of the groove 411 in the intermittent coating is 0.009 mm.

[0081] Example 3

[0082] Different from Example 1, the coating thickness of the polymer layer 3 on both sides of the battery separator in this embodiment is 0.0002 mm, wherein the coating method of the polymer layer 41 is intermittent coating, and the maximum depth of the groove 411 in the intermittent coating is 0.0015 mm.

[0083] Example 4

[0084] Different from Example 1, the coating thickness of the polymer layer 3 on both sides of the battery separator in this embodiment is 0.001 mm, wherein the coating method of the polymer layer 41 is intermittent coating, and the maximum width of the groove 411 in the intermittent coating is 0.8 mm.

[0085] Example 5

[0086] Different from Example 1, the coating thickness of the polymer layer 3 on both sides of the battery separator in this embodiment is 0.001 mm, wherein the coating method of the polymer layer 41 is intermittent coating, and the maximum width of the groove 411 in the intermittent coating is 1.0 mm.

[0087] Comparative Example 1

[0088] Different from Example 1, the base film 1 of the present application has a thickness of 0.004 mm, the first coating 3 (oily coating layer) has a double-sided coating thickness of 0.0015 mm, and the entire diaphragm area has only a double-sided first coating 3 (oily coating layer) without a polymer layer 41 coating.

[0089] Comparative Example 2

[0090] Different from Example 1, the base film 1 of the present application has a thickness of 0.004 mm, and the first coating 3 (oily coating layer) has a double-sided coating thickness of 0.0015 mm. The entire diaphragm area is only coated with the first coating 3 (oily coating layer) on both sides, wherein the polymer layer 41 has the same coating length as the first coating 3 and is distributed in both the straight section 11 and the curved section.

[0091] Among them, the detection method is as follows:

[0092] The cells prepared in Examples 1-5 and Comparative Examples 1-2 were respectively cycled at room temperature, and the test steps were as follows:

[0093] The charging mode is: 1.2C CC to 4.18V, CV to 0.7C or 0.7C CC to 4.50V, CV to0.05C; CC means constant current charging and CV means constant voltage charging.

[0094] Discharge mode: 0.5C DC to 3.0V, where DC means constant current discharge;

[0095] In the experimental data of Table 2 and Table 3 below in this application, capacity retention rate = weekly discharge capacity / initial discharge capacity*100%, thickness expansion rate = full-charge thickness per 100 weeks / initial full-charge thickness*100%.

[0096]

[0097] Table 2 Test capacity retention rate experimental data

[0098]

[0099]

[0100] Table 3 Experimental data of thickness expansion rate test

[0101] The data of the battery prepared by the above table data and the relevant diaphragms of Examples 1-5 and Comparative Examples 1-2, Figure 5 - Curve of the battery room temperature cycle capacity retention rate in Example 1 of the present invention and Comparative Example 1 and Figure 6- Curve diagram of the thickness expansion rate of the battery during normal temperature cycling in Example 1 of the present invention and Comparative Example 1. It can be seen that the battery cells prepared by the diaphragm of the present application are superior to the prior art in terms of capacity retention rate and thickness expansion rate. Specifically, after 1000 weeks of cycle testing, the capacity retention rate of the battery cells of Examples 1 to 5 was higher than 90%, while the battery cells of Comparative Examples 1 and 2 dropped to 84.2% and 86.7%, respectively. In terms of thickness expansion rate, the expansion rate of the battery cells of Examples 1 to 5 after 1000 weeks was lower than 7%, while the battery cells of Comparative Examples 1 and 2 reached 8.11% and 7.82%, respectively. This shows that the diaphragm preparation technology of the present application has significant advantages in the long-term performance of the battery cells.

[0102] Further analysis shows that the cells of Examples 1 to 5 show good stability during the cycle, which is mainly due to the optimized coating of the polymer layer 3 in the separator. By adjusting the coating thickness and coating method of the polymer layer 3, the porosity and mechanical strength of the separator can be effectively controlled, thereby improving the cycle life and safety of the cell. For example, in Example 2, the coating thickness of the polymer layer 3 is thin, but the depth of its groove 411 is large, which also helps to improve the air permeability of the separator, thereby reducing the gas pressure inside the battery and reducing thickness expansion.

[0103] In addition, the coating thickness of the polymer layer 3 in Examples 4 and 5 is the same, but the width of the groove 411 is different, which shows the influence of adjusting the coating method within a certain range on the performance of the battery cell. The groove 411 of Example 4 is smaller in width, which may help to improve the mechanical strength of the separator, while the groove 411 of Example 5 is larger in width, which may be more conducive to the penetration of the electrolyte and ion transport.

[0104] In summary, the diaphragm preparation technology of the present application significantly improves the cycle stability and safety of the battery cell by optimizing the coating thickness and coating method of the polymer layer 3.

[0105] The above are only preferred implementations of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the protection scope of the present application.

Claims

1. A diaphragm, suitable for a wound electrode assembly, wherein the electrode assembly (2) has a corner region (21) in a curved state, characterized in that: The diaphragm comprises: A base film (1), in a flattened state, along the length direction of the base film (1), the base film (1) comprises straight sections (11) and sections to be bent (12) which are alternately connected in sequence, and the sections to be bent (12) correspond to the corner areas (21); A first coating layer (3) is respectively disposed on two surfaces of the base film (1) along the thickness direction thereof; A second coating (4) is arranged on at least one side of the base film (1) along the thickness direction thereof, and the second coating (4) is arranged between the base film (1) and the first coating (3); The second coating layer (4) comprises a plurality of polymer layers (41), wherein the plurality of polymer layers (41) are arranged at intervals along the length direction of the base film (1); the polymer layers (41) are arranged corresponding to the to-be-bent segment (12); Wherein, at least one of the polymer layers (41) is provided with at least two grooves (411).

2. The diaphragm according to claim 1, characterized in that The electrode assembly (2) comprises a pole piece (22) in a wound structure, wherein the pole piece (22) is in contact with the diaphragm; the length of the polymer layer (41) corresponding to the section to be bent (12) is L1, and the diaphragm has a recessed area and a raised area in the section to be bent (12), and the arc length of the raised area is L2, wherein L1 and L2 satisfy: L2≥L1≥0.8L2.

3. The diaphragm according to claim 2, characterized in that The arc diameter of the raised area of ​​the to-be-bent section (12) of the innermost layer of the diaphragm is Ds0, and the arc length L corresponding to the raised area of ​​the to-be-bent section (12) of the innermost layer of the diaphragm is 21 Meet L 21 =π(Ds0) / 2.

4. The diaphragm according to claim 3, characterized in that The number of winding layers of the diaphragm is n, and the arc length L of the convex area corresponding to the nth winding layer of the diaphragm in the to-be-bent section (12) is 2n Meet L 2n =π(Ds0+(N-1)△t) / 2; Wherein, for each additional layer of winding of the diaphragm on the basis of the innermost layer, the increase in the diameter of the circular arc corresponding to the raised area of ​​the diaphragm in the to-be-bent section (12) relative to the diameter of the circular arc corresponding to the raised area of ​​the adjacent inner diaphragm in the to-be-bent section (12) is Δt.

5. The diaphragm according to claim 1, characterized in that Along the length direction of the polymer layer (41), the width of the groove (411) increases first and then decreases, and the width of the groove (411) corresponding to the length center of the section to be bent (12) is the largest.

6. The diaphragm according to claim 5, characterized in that The width of the groove (411) is D1, and D1 satisfies: 0.9 mm-1.1 mm.

7. The diaphragm according to claim 1, characterized in that Along the length direction of the polymer layer (41), the depth of the groove (411) increases first and then decreases, and the depth of the groove (411) corresponding to the length center of the section to be bent (12) is the largest.

8. The diaphragm according to claim 7, characterized in that The depth of the groove (411) is D2, and D2 satisfies: 0.5 micrometers to 10 micrometers.

9. The diaphragm according to claim 1, characterized in that The polymer layer (41) comprises an emulsion of polymer particles, a dispersion aid and an adhesive; The emulsion of the polymer particles is one or more of polyethylene emulsion, polyethylene microwax emulsion, polyvinylidene fluoride emulsion, polytetrafluoroethylene emulsion, polymethyl methacrylate emulsion, polyimide emulsion, polystyrene emulsion and polyacrylamide emulsion; The dispersing auxiliary agent is one or more of polyacrylic acid and its sodium salt, polyacrylamide, polyvinyl alcohol, sodium citrate, sodium ethylenediaminetetraacetate, sodium diacetate, sodium hexametaphosphate, sodium silicate, and carboxymethyl cellulose; The adhesive is a polypropylene adhesive.

10. A secondary battery, characterized in that: Comprising the diaphragm as described in any one of claims 1-9.

Citation Information

Patent Citations

  • Composite battery diaphragm, preparation method and battery

    CN108711605A

  • Diaphragm for lithium-ion battery and lithium-ion battery containing diaphragm

    CN110010831A

  • Winding battery diaphragm, winding battery and vehicle

    CN115117557A

  • Diaphragm, roll core and battery

    CN115332727A

  • Battery diaphragm, battery cell and lithium ion battery

    CN219498085U

Cited By

  • Secondary battery and electric device

    CN121035532A